2011
DOI: 10.3171/2011.5.jns101615
|View full text |Cite
|
Sign up to set email alerts
|

Two-level motor nerve transfer for the treatment of long thoracic nerve palsy

Abstract: The authors report a case of long thoracic nerve (LTN) palsy treated with two-level motor nerve transfers of a pectoral fascicle of the middle trunk, and a branch of the thoracodorsal nerve. This procedure resulted in near-total improvement of the winged scapula deformity, and a return of excellent shoulder function. A detailed account of the postoperative physical therapy regimen is included, as this critical component of the favorable result cannot be overlooked. This case establishes the two-level motor ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The proposed clinical decision-making algorithm presented in this article takes into consideration the work of other surgeons by including both proximal and chest-level decompression, as well as advances in nerve transfers to improve function in this patient population. 4,5,10,19,20,23,24 Further evaluation and refinement of the algorithm is ongoing as we treat more patients with a multilevel surgical approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed clinical decision-making algorithm presented in this article takes into consideration the work of other surgeons by including both proximal and chest-level decompression, as well as advances in nerve transfers to improve function in this patient population. 4,5,10,19,20,23,24 Further evaluation and refinement of the algorithm is ongoing as we treat more patients with a multilevel surgical approach.…”
Section: Resultsmentioning
confidence: 99%
“…23 Ray et al reported the first 2-level nerve transfer for the long thoracic nerve palsy in a patient with isolated long thoracic nerve palsy. 19 In this case, the patient had a proximal medial pectoral nerve to long thoracic nerve transfer and a distal thoracodorsal to long thoracic nerve transfer. 19 There is no consensus in the literature regarding the best management of isolated long thoracic nerve palsy.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on the anatomical features, the expendability of C7 pectoral fascicles within the brachial plexus can be understood (David et al., 2010). Many authors have reported the clinical use of pectoral fascicles as donors in BPI reconstruction, without significant postoperative deficits (Maldonado and Spinner, 2017; Ray et al., 2011and 2012; Songcharoen et al., 2001; Wang et al., 2012; Yin et al., 2012). By harvesting a single C7 motor fascicle as we describe, the risk of a postoperative deficit appears to be low.…”
Section: Discussionmentioning
confidence: 99%